2016
DOI: 10.4149/neo_2016_508
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-182 suppresses clear cell renal cell carcinoma migration and invasion by targeting IGF1R

Li H2,
et al.

Abstract: The purpose of our study was aimed to determine the functional role of microRNA (miR)-182 in clear cell renal cell carcinoma (ccRCC) and try to clarify its underlying molecular mechanism. Expression of miR-182 in both cancer and peripheral blood samples was analyzed by quantitative real-time PCR (qRT-PCR). Human RCC line Caki-1 cells were transfected with miR-182 mimic, miR-182 inhibitor, or negative controls, and then the cell viability, colony-formation ability, migration, and invasion assay were determined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…However, the function of miR-182-5p is complicated because it can be an oncogene or a tumor suppressor in the context of different cancers. miR-182-5p is identified as onco-miR in ovarian cancer [ 6 ], breast cancer [ 7 ], and melanoma [ 8 ] and acts as tumor suppressor in RCC [ 9 , 10 ] and glioblastoma [ 11 , 12 ]. In HCC, miR-182-5p contributes to HCC metastasis by targeting metastasis suppressor 1 (MTSS1) [ 13 ], and upregulated miR-182-5p increases drug resistance in cisplatin-treated HCC cells by regulating tumor protein 53-induced nuclear protein 1 (TP53INP1) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the function of miR-182-5p is complicated because it can be an oncogene or a tumor suppressor in the context of different cancers. miR-182-5p is identified as onco-miR in ovarian cancer [ 6 ], breast cancer [ 7 ], and melanoma [ 8 ] and acts as tumor suppressor in RCC [ 9 , 10 ] and glioblastoma [ 11 , 12 ]. In HCC, miR-182-5p contributes to HCC metastasis by targeting metastasis suppressor 1 (MTSS1) [ 13 ], and upregulated miR-182-5p increases drug resistance in cisplatin-treated HCC cells by regulating tumor protein 53-induced nuclear protein 1 (TP53INP1) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a study by Wang et al revealed that IGF1R, another tyrosine kinase receptor, is a direct target gene of miR‐182, and miR‐182 suppresses the migration and invasion in clear cell renal cell carcinoma . Based on our findings that miR‐182 suppressed HGF‐induced phosphorylation of AKT, we inquired whether miR‐182 also suppressed IGF‐induced phosphorylation of AKT and suppressed the tumor cell EMT process.…”
Section: Discussionmentioning
confidence: 78%
“…D, A549 cells were transfected with miR-182 or control scrambled oligonucleotides and then treated with HGF for different time periods (0 h, 15 min, 30 min, 1 h, 2 h, and 12 h), and the expressional change in E-cadherin was measured in these cells by Western blotting analysis. E, A549 cells were transfected with miR-182 or Met siRNA or a combination of control miR-182 and Met siRNA or scrambled oligonucleotides and then stimulated with or without HGF for 2 h. The expressional change in E-cadherin was measured in these cells by fluorescent immunocytochemical analysis carcinoma 28. Based on our findings that miR-182 suppressed HGFinduced phosphorylation of AKT, we inquired whether miR-182 also suppressed IGF-induced phosphorylation of AKT and suppressed the tumor cell EMT process.…”
mentioning
confidence: 99%
“…In the present study, we identified 17 DEmiRNAs in the ceRNA network. Among them, several miRNAs have been reported to play important roles in the initiation and development of RCC, such as miR-182, miR-136, and miR-629 [31][32][33]. To further identify the key circRNAs participating in the regulatory network, we established the PPI network, thereby screening 8 hub genes.…”
Section: Discussionmentioning
confidence: 99%